Health Equity Considerations: HIV Intervention Adaptation for Black Women in Community Corrections. (March 2023) - Johnson, Karen A.; Hunt, Timothy; Goddard-Eckrich, Dawn; Wu, Elwin; Richards, Stanley; Tibbetts, Rick; Rowe, Jessica C.; Maynard, Quentin R.; Goodwin, Sharun; Okine, Joana; Wainberg, Milton L.; El-Bassel, Nabila; et al.
Objectives: This article describes the process used to adapt the only group-based, computer-assisted, HIV/sexually transmitted infections (STI) prevention intervention designed for drug-using Black women in community corrections using an integrated health equity ADAPT-ITT framework with a peer engagement lens.Methods: Key adaptation partners included cisgender, drug-using Black women in community corrections, and Black, female, community reentry providers slated to deliver the adapted intervention. Focus groups and a study pilot were held.Results: The resulting intervention, Empowering African-American Women on the Road to Health (E-WORTH), features HIV/STI-specific Afrocentric themes of risk and resiliency tailored for and by Black women in the criminal legal system. Evaluation of E-WORTH confirms its cultural resonance. Participants had a 54% lowered odds of testing positive for any STI and reported 38% fewer acts of condomless vaginal or anal intercourse at 12-month follow-up.Conclusions: Findings underscore the need to develop an adaptation model that is explicitly health equity in focus.